THE STUDENT’S ENHANCEMENT OF MULTIPLE REPRESENTATION ABILITY USING MERRILL’S FIRST PRINCIPLES OF INSTRUCTION - Hestu Wilujeng; Retno Andriyani (FKIP Universitas Muhammadiyah Tangerang, 2022)
A learning process in schools realizes the purpose of this education. Mathematical multi representation ability is one of the general goals of teaching mathematics in schools. This research is quasi-experimental. The amount of increase before and after learning is calculated by the normalized gain formula. There is a difference in the increase in mathematical multi-representation abilities of students who receive MFPI learning than conventional learning based on high KAM and medium early mathematical ability. By contrast, at low early mathematical ability, there is no difference in increasing multi representation abilities. Most students use mathematical representations. The percentage of students using more than two representations is 40%. MFPI learning affects students with high and medium KAM but does not affect students with low early mathematical ability. Because at the MFPI learning stage, low early mathematical ability students lack initial knowledge that can be used to form new knowledge.